Răspunsuri

2014-11-16T17:00:09+02:00
25x^2-10x+1-(x^2+8x-6x-48)=85                                                                          25x^2-10x+1-x^2-2x+48=85                                                                                24x^2-12x+49=85                                                                                               24x^2-12x-36=0                                                                                                 delta=12*12+4*36*24=3600                                                                                   x1=(12+60)/48=1,5                                                                                             x2=(12-60)/48=-1